Existence of periodic solutions of a nonlinear Allen-Cahn equation with Neumann problem - Taha, Wafaa; Hameed, Raad; Sarah Majeed Talab (Al-Qadisiyah Journal of Pure Science, 2020)
This research investigated the periodic solutions to a nonlinear diffusion Allen-Cahn equation with isolated Neumann problem. The theory of Leray-Schauder fixed point degree was adopted and the study showed that there exist nontrivial periodic solutions to the nonlinear diffusion Allen-Cahn equation with isolated Neumann problem by the topological degree theory.